Minor Sentence Link in The Noble Qur’an - Mosalam, Alwaleed Hassan Ali (Journal of Arabic Language Sciences and Literature, 2023)
This research was conducted to address the link that connects the minor sentence that is news to the subject within the space of the major sentence in the Holy Qur’an, grammatically, and the descriptive analytical method was followed in writing it, and it was divided into three sections, the first: the definition of the terms link and the minor sentence, and the second topic: the type of link of the small sentence In the Noble Qur’an and its implications, and the third topic: the deletion of the link of the minor sentence in the Noble Qur’an, and results were reached, the most important of which are: the frequent coming of the link of the minor sentence as a pronoun, and the pronoun diversified between prominent and hidden, and richer than the pronoun in linking the nominative sign, the apparent noun, and the return of the subject With its wording, the alif and the lam among the Kufics, and the connotations of the link represented in emphasizing, glorifying, exaggerating, exaggerating, general, and restricting, and the link of the minor sentence and the pronoun was omitted in the abnormal Qur’anic readings in abundance, unlike the frequent readings.
Keywords: grammatical studies in the Qur'an; the small sentence; the links